Kinetic-Catalytic-Spectrophotometric Determination of Ultra Trace Amounts of Rhodium(III) by Its Catalytic Effect on The Oxidation of SPADNS by Metaperiodate in Micellar Media - KEYVANFARD, MOHSEN (Asian Journal of Chemistry, 2010)
A new, sensitive and simple kinetic spectrophotometric method was developed for the determination of ultra trace amounts of Rh(III). The method is based on the catalytic effect of Rh(III) on the oxidation of sodium 2-(p-sulfophenylazo)-1,8-dihydroxy-naphthalene-3,6-disulfonate (SPADNS) by metaperiodate at pH 7.5 in micellar media. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of SPADNS at 517 nm with a fixedtime method.The decrease in the absorbance of SPADNS is proportional to the concentration of Rh(III) in concentration range 1.0-250.0 ng/mL, with a fixed time of 0.5-4.5 min from initiation of the reaction. The limit of detection is 0.77 ng/mL Rh(III).The relative standard deviation of 0.020 and 0.040 μg/mL Rh(III) was 1.9 and 2.3 %, respectively. The method was applied to the determination of rhodium in water sample and synthetic water sample.